الديمقراطية التشاركية، وأدواتها الرقمية، منطلقات نظرية، وتطبيقات عملية - فورار, أحمد أمين (University of Eloued جامعة الوادي, 2018)
دفعت بعض جوانب القصور في ممارسة الديمقراطية التمثيلية، إلى الدعوة لتبني نوع آخر من الديمقراطية أكثر قدرة على إشراك المواطنين في اتخاذ القرار بما يحقق جوهر العملية الديمقراطية، فتم إعادة تبني ممارسة معروفة تاريخيا بالديمقراطية التشاركية بهدف خلق مزيد من الفرص والأدوات أمام الأفراد للمساهمة في صنع القرار. يعتمد تطبيق الديمقراطية التشاركية حاليا بشكل متزايد على أدوات المشاركة الإلكترونية من خلال استخدام خلال تقنيات المعلومات والاتصالات بهدف تعزيز المشاركة المدنية والحكم التشاركي الشفّاف. تتناول هذه الورقة البحثة المنطلقات النظرية الداعية لتبني الديمقراطية التشاركية اعتمادا على نقل تصورات الباحثين، إلى جانب التطرق لأدواتها الرقمية بالتحليل، اعتماد على بعض التجارب في هذا المجال. Abstract There are some insufficiencies in the practice of representative democracy that have led to the adoption of a different kind of democracy which is more capable of involving citizens in decision-making in order to fulfill the democratic process. Thus, a participatory democracy which is known historically has been re-adopted with the objective of creating more opportunities and tools to make the population involve in decision-making. It mainly tries to overcome the issue of representation, and ensure popular participation through the application of mechanisms that guarantee the involvement of everyone in decision-making, control and initiative. The application of participatory democracy depends increasingly on tools of electronic participation through ICT (Information and communication technologies) in order to reinforce civil participation and transparent participatory governance. This paper deals with the theoretical principles that calls for the adoption of participative democracy based on the perceptions of researchers, in addition to the analysis of their digital tools, relying on some experiences in this field.
Participatory democracy, its digital tools, theoretical premises, and practical applications
مجلة البحوث والدراسات المجلد 15 العدد01 جامعة الوادي
Keywords: الديمقراطية التشاركية، المشاركة الإلكترونية، المواطنة الرقمية، البوابات الحكومية، العرائض الإلكترونية، جاهزية الحكومة الإلكترونية; Participatory democracy; Electronic participation; Information and communication technologies